Description of the Behavior of using Personal Protective Equipment and Personal Hygiene on Workers who Transport Waste - Flavianus Kostka Sarman; Sony Doke; Honey Ivone Ndoen (Universitas Nusa Cendana, 2022)
The use of personal protective equipment and personal hygiene is an important thing that needs to be applied by garbage collectors to minimize the risk of accidents and occupational diseases. This study aimed to determine knowledge, use of PPE, supervision and personal hygiene in waste transport works at the Manggarai Regency Environmental service. The sampling technique used total sampling with a sample of 53 subjects. The results showed that the level of knowledge was categorized as good 27 (50.09%) respondents, moderate, 20 (37.8%) respondents, and low 6 (11.3%) respondents, and the level of use of PPE was 53 (100%) respondent using in complete PPE, the level of supervision 29 (54.71%) respondents said there was no supervision, and 24 (45.28 %) respondents said there was supervision and the level of personal hygiene 47 (88.7%) respondents were categorized as good and 6 (11.3%) respondents are categorized as bad. The Regional Environmental Service of Manggarai Regency should conduct socialization related to personal protective equipment and personal hygiene and supervise PPE use.